PROBLEMATIKA KETERAMPILAN MEMBACA PERMULAAN PESERTA DIDIK KELAS RENDAH PADA PEMBELAJARAN BAHASA INDONESIA SEKOLAH DASAR - Purnamasari, Evi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Early reading is a very important basic skill for elementary school students, especially in the lower grades. Students often face difficulties in developing their reading skills. This article aims to identify the problems of early reading skills and the factors that influence them. The research method used is a qualitative method using case studies and a descriptive approach. The results of the study explain that the main problems in early reading include difficulty in recognizing letters, lack of understanding of the meaning of reading, and low interest in reading. Factors that play a role and influence include ineffective learning methods, a less supportive reading environment, and differences in cognitive abilities of each student. Educators are expected to be able to develop more effective learning strategies to improve students' reading skills.